Euclidean Shortest Paths: Exact or Approximate Algorithms - Li, Fajie; Klette, Reinhard (Springer London, Limited, 2011)
This book reviews algorithms for the exact or approximate solution of shortest-path problems, with a specific focus on a class of algorithms called rubberband algorithms. The coverage includes mathematical proofs for many of the given statements.